Urban Areas and Territorial Cohesion Objective: Actual Strategies and Future Challenges - Loris Servillo (European Regional Science Association (ERSA), 2006)
The EU's ever-tightening focus on an urban agenda has led it, in recent years, to a clear recognition of cities as motors of regional, national and thus European development. Cities appears as crucial nodes, as centres of excellence of european territory, that can drive economic competitiveness and, at the same time, can forge territorial cohesion – itself an essential condition for the growth of long-term competitiveness. The opportunity to explicitly pursue the territorial dimension of cohesion will take substance with the forthcoming programming period. As cities seem to be crucial for the aim of a more coherent spatial framework of European development, urban policies will be one of the pillar of European Cohesion policy beeing strongly linked with territorial cohesion. From a strategic point of view, the Commission has proposed a new planning system which is of considerable significance for the territorial cohesion agenda, based on Community Strategic Guidelines and National Strategic Reference Framework governing the delivery of individual operational programmes, with the intention of to ensuring that overarching EU policy objectives are clearly reflected in the allocation of resources. The guidelines specifically will refer to the key issue of urban areas, suggesting the need to support competitiveness of neighboring cities. However how this aim will be tackled in practice depends on a number of issues. The thesis of the paper is about the various topics, emerging from the EU praxis, that seems relevant about urban policies: the urban and territorial governance, the "territorialization" of infrastructural projects, the urban policentric systems and city–region concept, the urban quality and renewaling instrument, the transnational cooperation and the urban networks. As well as taking into account the new context for territorial cohesion and urban policy, it is important to take stock of past experience and policy practice. Reletad, to understand how future urban policies might support territorial cohesion, it is worth considering how key measures have been implemented and what kind of tipologies it is possible to identify. The ESPON projects 2.3.1. and 2.3.2 will be the part of the core research field in which to extrapolate cases studies and analysis references.
Keywords: 330